Applying the priority distribution method for employee motivation - Žaptorius, Jonas (Business, Management and Economics Engineering, 2013)
In an age of increasing healthcare expenditure, the efficiency of healthcare services is a burning issue. This paper deals with the creation of a performancerelated remuneration system, which would meet requirements for efficiency and sustainable quality. In real world scenarios, it is difficult to create an objective and transparent employee performance evaluation model dealing with both qualitative and quantitative criteria. To achieve these goals, the use of decision support methods is suggested and analysed. The systematic approach of practical application of the Priority Distribution Method to healthcare provider organisations is created and described.